Paul Farmer : élaboration d’une représentation collective du sida en zone rurale d’Haïti au prisme du contexte historique et géopolitique haïtien (1983-1990) - Dolorès Pourette (Genre, Sexualité et Société)
This text, published in 1990, presents an anthropological study of the development of a collective representation of AIDS in rural Haiti between 1983 and 1990. Paul Farmer, a physician and medical anthropologist, highlights how local experiences and interpretations of AIDS, the subjective experience of the disease, and the discursive practices around AIDS are are profoundly affected by the sociohistorical and geopolitical context of the region, especially relations with the Hatian capital and the United States. The lessons of this text, both theoretical and methodological, remain relevant to contemporary issues in medical anthropology.